Subsurface Band Placement of Pelletized Poultry Litter in Cotton. (1st July 2016) - Adeli, Ardeshir; McCarty, Jack C.; Read, John J.; Willers, Jeffrey L.; Feng, Gary; Jenkins, Johnie N.
Abstract : Alternative management of broiler chicken (Gallus gallus domesticus ) litter in cotton ( Gossypium hirsutum L.) production is needed to enhance soil fertility, crop nutrient utilization, and lint yield. This 4‐yr study compared the growth, lint yield, and soil quality in cotton production systems fertilized with pelletized poultry litter (PPL) subsurface band applied at the rate of 6.7 Mg ha −1 (≈122 kg available N ha −1 ), inorganic N fertilizer (urea ammonium nitrate, UAN solution) injected at the recommended rate of 128 kg N ha −1, and unfertilized control. Drip irrigation was used as main plot, flue gas desulfurization (FGD) gypsum was broadcast applied and used as subplot, and fertilization treatment was used as sub‐subplot (2 × 2 × 3). Although leaf chlorophyll content, leaf area index and total aboveground biomass were lower ( P < 0.05) with PPL than inorganic N, lint yield did not differ between these treatments in 2010 and 2011. However, lint yield was greater in PPL than inorganic N fertilizer treatment by approximately 6% in 2012 and 21% in 2013. Averaged across years, lint yield was 5% greater with PPL than inorganic N fertilizer (1378 vs. 1303 kg ha −1 ). Cotton lint yield was not influenced by FGD gypsum or irrigation. Applying PPL significantly enhanced soil fertility, improved soil aggregate stability, minimized postharvest residual NO3 –N concentration in the soil profile and may provide growers with an alternative nutrient management strategy for cotton. Core Ideas Subsurface band placement minimizes nutrient loss. Subsurface band placement of pelletized poultry litter increases nutrient utilization. Pelletized poultry litter improves soil quality by enhancing soil organic C.